2019
DOI: 10.24275/rmiq/alim581
|View full text |Cite
|
Sign up to set email alerts
|

RHEOLOGICAL CHARACTERIZATION OF GUMS-GEL OBTAINED FROM THE PROTEIC ISOLATE OF SESAME (Sesamum indicum)

Abstract: Modelado de la biodegradación en biorreactores de lodos de hidrocarburos totales del petróleo intemperizados en suelos y sedimentos (Biodegradation modeling of sludge bioreactors of total petroleum hydrocarbons weathering in soil and sediments)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…Both essential fatty acids are important in the human feed, because they offer health benefits. In the last years has been reported that the consumption of sesame oil influences in blood lipid profiles, increasing antiinflammatory function, and exhibiting antimutagenic activity (Moreno-Santander et al, 2020;Xu-Yan et al, 2012). For this reason, numerous efforts have been made to fortify foods with ω-3e6 fatty acids to achieve a balanced intake.…”
Section: Introductionmentioning
confidence: 99%
“…Both essential fatty acids are important in the human feed, because they offer health benefits. In the last years has been reported that the consumption of sesame oil influences in blood lipid profiles, increasing antiinflammatory function, and exhibiting antimutagenic activity (Moreno-Santander et al, 2020;Xu-Yan et al, 2012). For this reason, numerous efforts have been made to fortify foods with ω-3e6 fatty acids to achieve a balanced intake.…”
Section: Introductionmentioning
confidence: 99%
“…De hecho, estas proteínas son renovables y cuentan con interesantes propiedades funcionales y/o fisicoquímicas (Nesterenko et al, 2013). Se ha demostrado que las proteínas vegetales son adecuadas para la estabilización de emulsiones multicapa y para la formación de geles (Moreno-Santander et al, 2020). Además, las proteínas vegetales se pueden combinar con otros polímeros comestibles para mejorar la calidad y el valor nutricional de los productos alimenticios .…”
Section: -Introducciónunclassified